Analisis Faktor-Faktor Penyebab Piutang Tak Tertagih Pada Perumda Air Minum Tirta Batang Hari - Fauziah Fauziah (CITRA EKONOMI, 2022)
This study aims to analyze the internal factors and external factors that cause bad debts at Perumda Water Drinking Tirta Batang Hari. The data of this research were obtained from direct (primary) interviews with the Perumda Water Drinking Tirta Batang Hari and several other documents. In this study, the author uses a descriptive qualitative analysis technique, where after the data is collected, analyzed and processed to provide a reasonable description and description of the state of the object of research. is negligence on the part of creditors in complying with the approval of the granting of credits that have been affirmed, it is too easy to give receivables due to the lack of clear benchmarks on wealth standards, shortage of staff/staff for receivables collection, and the company's weakness in detecting the emergence of bad debts including detecting the direction of the development of user cash flows. services or old debtors. Meanwhile, the external factor is the decline in the company's economic condition caused by the decline in general economic conditions and or the business field in which they operate, and the bad character of the debtor (who originally planned not to pay off his receivables).